The Role of Legal Sociology in Understanding the Dynamics of Law Enforcement in Society - Afnaini Afnaini; Hamdan Hamdan (Jurnal Restorasi : Hukum dan Politik, 2026)
Law enforcement in Indonesia is not only a process of formally implementing legal norms but is also influenced by social, cultural, political, and economic conditions in society. This study aims to analyze the role of legal sociology in understanding the dynamics of law enforcement in society, particularly in explaining the gap between normative law and empirical legal practice. This study uses a qualitative approach with a critical perspective through exploratory literature review of legislation, legal sociology literature, and scholarly articles from reputable journals. Data analysis was conducted using a thematic approach to identify social patterns, societal legal behavior, and structural factors that influence the effectiveness of law enforcement. The results indicate that legal sociology plays a crucial role in bridging the gap between written law and social reality, analyzing social factors in legal implementation, assessing the effectiveness of law as a tool of social control, and providing input for the formulation of more responsive and equitable legal policies. This study confirms that integrating a legal sociology perspective into law enforcement is necessary to create a legal system that not only guarantees legal certainty but also substantive justice and social benefits for society.